Prizes for the 1986 y-Walk participants - Unknown:::Creator::::::::::::
Negative shows a group of men and women who are y-walk participants gathered around Jenifer Williams in the YWCA parking lot. Jenifer, who is the chair and appears to be African American, is standing with another women at a microphone. She may be giving out prizes to participants. There are plants on a table next to Jenifer which are probably prizes. Some of the participants watching are holding balloons and some of the people are holding drinks. Many of them are wearing tee shirts that read: Walk for women. "YWCA 1986."